Assessment of Risk Tendency of Coal Bursting Pressure in Deep Outburst Seam. (29th May 2022) - Gu, Beifang; Wang, Longkang; Zhang, Minbo
Abstract : In order to analysis the mechanism of coal bursting pressures of deep coal seams and take effective methods to identify, monitor, and control coal bursting pressure, this paper takes 21101 working face of No. 2 coal seam in Dongpang Coal Mine as an example. Risk identification is carried out for the hazardous and harmful factors of coal bursting pressure in coal seam 21101 in Dongpang Coal Mine, and each influencing factor is classified. The hierarchical structure model of the influencing factors of coal bursting pressure in coal seam protruding deep in Dongpang Coal Mine is established in combination with expert opinions, and the weight of each level index is calculated by MATLAB software. The results show that the 21101 working face of No. 2 coal seam in Dongpang Coal Mine has strong impact risk, and the main risk factors include geological structure, impact resistance of coal and rock, mining stress, inducing factors, and emphasis degree of impact risk. According to the results, the corresponding safety measures are put forward to prevent the damage caused by coal bursting pressure in advance and ensure the high quality and safe production in the mine. The qualitative and quantitative methods are used to make the evaluation process more reasonable and scientific. The method could effectively analyze the main factors affecting coal bursting pressure and put forward corresponding safety measures for the main risk factors.